A Novel Power Grid Restoration Scheme Using Active PFC. (2015) - Joglekar, Jayesh; Gopalakrishnan, N.; Nerkar, Y.P.
Abstract: The Distributed Generator (DG) based intentional islanding is very useful and improves the stability of power system. But the inverter based connection of DG leads to power quality related issues like harmonics injunction, voltage flicker and non-sine wave output. As a remedy, modeling and control of fuel cell based distribution generation system is studied and implemented for Thermal Power Station (TPS) for improving power system reliability. The TPS auxiliaries which are receiving power from station transformer during healthy system conditions, stop functioning during faulty grid conditions as it is difficult to fulfill their power demand. The paper proposes a novel method for running TPS auxiliaries during system disturbance using fuel cell as an alternative source of power. The voltage profile in the proposed method is maintained using power flow controller (PFC). The multi converter power flow controller is used for easy power and voltage profile control. It is observed that separate use of fuel cell as a DG and Generalized Unified Power Flow Controller (GUPFC) as a PFC fail to show desired results. The proposed method is studied and simulated with standard IEEE and real time test systems. It is observed that using proposed method uninterrupted working of TPS auxiliaries is possible during condition of system disturbance. This unaffected TPS system is identified as a source of power during system restoration which is followed by grid disturbance.